2020
DOI: 10.1002/ijgo.13296
|View full text |Cite
|
Sign up to set email alerts
|

Performing gynecologic cancer surgery during the COVID‐19 pandemic in Turkey: A multicenter retrospective observational study

Abstract: Objective To report the perioperative outcomes of 200 patients with gynecologic cancer who underwent surgery during the Novel Coronavirus Disease (COVID‐19) pandemic and the safety of surgical approach. Methods Data of patients operated between March 10 and May 20, 2020, were collected retrospectively. Data were statistically analyzed using IBM Statistical Package for the Social Sciences (SPSS) Statistics for Windows v. SP21.0. Results Data of 200 patients were included. Their mean age was 56 years. Of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 21 publications
5
34
0
Order By: Relevance
“…The Meta-Analysis showed that the prevalence of comorbidity among surgical patients was with COVID-19 was 18% (95% CI: 10 to 25) which is in line with the results of included studies (21,23,29,49,90,91,95). The subgroup analysis showed that dementia was the most prevalent comorbidity followed by hypertension and Diabetes Mellitus.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The Meta-Analysis showed that the prevalence of comorbidity among surgical patients was with COVID-19 was 18% (95% CI: 10 to 25) which is in line with the results of included studies (21,23,29,49,90,91,95). The subgroup analysis showed that dementia was the most prevalent comorbidity followed by hypertension and Diabetes Mellitus.…”
Section: Discussionsupporting
confidence: 80%
“…Body of evidence showed that patients visiting the health institution during the COVID-19 pandemic decrease signi cantly despite requiring medical care which affects signi cantly the non-COVID-19 patients' hospital admission (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body of evidence showed that patients visiting the health institution during the COVID-19 pandemic decrease signi cantly despite requiring medical care which affects signi cantly the non-COVID-19 patients' hospital admission [29][30][31][32][33].…”
mentioning
confidence: 99%
“…Some studies showed that perioperative mortality of patients with COVID-19 was very high [30,32,46,[55][56][57] while some studies failed to identify signi cant mortality among patients with COVID-19 undergoing surgical procedures [28,54,58,59].…”
mentioning
confidence: 99%